Overthinking Pada Mahasiswa: Analisis Perbandingan Mahasiswa Tingkat Awal dan Tingkat Akhir - Ivanka, Dea; Dinata Saragi, Muhammad Putra (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
This study aimed at overthinking in early and final-year students from UINSU and non-UINSU students. This research approach is a mixed method (Mixed Quantitative and Qualitative Methods). Both approaches are descriptive. Quantitative research, in the process of collecting data by distributing questionnaires online using the Google form and distributed from 12-20 February 2023. The results of distributing the online questionnaires were 200 respondents. Two measurement scales are used in descriptive quantitative research, namely "PTQ and PSWQ." Data processing in descriptive quantitative was assisted by SPSS version 22. Descriptive qualitative research collected data through interviews with the five informants from UINSU students in semesters 2, 4, 6, and 8. The interview process was conducted on February 24, 2023. Qualitative research This description helps validate the results of descriptive quantitative research. The validation carried out in this study used a structured research interview of 7 questions. Based on the measuring scale, namely the PTQ and PSWQ scales, the study results are that overthinking in early and final level students has the same categorization position, namely moderate categorization. Therefore, it is true that overthinking for students in the initial and final grades is true. This aligns with the validation results of research interviews with a descriptive qualitative approach to the five informants. That student will never be separated from overthinking both students in the early and final levels. For initial and final year students who experience the overthinking phase more often, namely final year students.